THE IMPACT OF POLICIES DURING COVID-19 BY FACTORS AFFECTING THE HUMAN DEVELOPMENT INDEX IN SOLORAYA USING REGRESSION METHOD - Ulfah Sulistyowati; Merlin Swantamalo Magna (Yayasan Education and Social Center, 2023)
Acommotion, COVID-19 is a significant phenomenon that occurs not only in Soloraya but also around the world. It is undeniable that the emergence of this phenomenon affects many sectors, one of which is regional development. Regional development itself can be measured by how good the human resources are. So this study wants to see if any changes have occurred during COVID-19. From the social and population sectors. The analysis used was regression with a significance level (α) of 5%. As a result, unemployment, poverty, and crime have a significant impact on HDI in the Soloraya region. Bps Central Java data in 2021 shows that the HDI of Surakarta City from 2016 to 2020 has experienced an increase in development, from 80.76 to 82.21. This condition is relevant to the development of the figures achieved in Central Java Province, both of which have increased. At the policy level, regional leaders focus on controlling the spread of COVID-19 as stated in the Circular Letter of the Mayor of Surakarta Number 067/036 concerning the Implementation of Restrictions on Community Activities to Control the Spread of CoronaVirus Disease 2019 (Covid-19) in Surakarta City, thus affecting efforts to suppress the hampered HDI numbers